Predictors of readmission in a medical department of a tertiary university hospital in the Philippines - Janika Adrienne L. Balane; Celina Daia DG. Yap; Cary Amiel G. Villanueva; Lia Aileen M. Palileo-Villanueva; Diana R. Tamondong-Lachica (BMC Health Services Research, 2023)
Abstract Background Identifying factors that increase the risk for hospital readmission helps in determining potential targets for quality improvement efforts. The main objective of this study was to examine factors that predict increased risk of hospital readmission within 30 days of hospital discharge of patients under the General Medicine service of a tertiary government hospital in Manila, Philippines. Methods We performed a retrospective cohort study which included service patients 19 years old and above readmitted within 30 days following discharge. A total of 324 hospital readmissions within 30 days of discharge from January 1 to December 31, 2019 were reviewed. We estimated the rate of 30-day readmission and identified factors associated with preventable readmissions using multivariable logistic regression. Results Of the 4,010 hospitalizations under General Medicine service in 2019, 602 (18%) were readmissions within 30 days of discharge, majority of which were related to the index admission (90%) and unplanned (68%). Predictors of preventable readmission were emergency readmission (OR 3.37, 95% CI 1.72 to 6.60), having five to ten medications at discharge (OR 1.78, 95% CI 1.10 to 2.87), and presence of nosocomial infection (OR 1.86, 95% CI 1.09 to 3.17). The most frequent reason for readmission among preventable ones is health-care related infection (42.9%). Conclusions We identified factors which increased the likelihood of preventable readmissions such as type of readmission, number of medications per day, and presence of nosocomial infections. We propose that these issues be addressed to improve healthcare delivery and reduce readmission-related expenditures. Further studies should be pursued to identify impactful evidence-based practices.